Effective antihypertensive therapy: focus on adherence management - S. S. Bunova; N. I. Zhernakova; M. M. Fedorin; Y. P. Skirdenko; O. A. Osipova (Кардиоваскулярная терапия и профилактика, 2020)
High medical adherence is a prerequisite for achieving goals in the treatment of hypertension (HTN). The majority of patients with HTN showed low adherence to treatment, which requires finding ways to solve this problem. This review describes the factors influencing adherence, ways of its assessment, and analyzes methods of increasing medical adherence in hypertensive patients. Noteworthy is the lack of publications describing the effectiveness of methods for increasing long-term (>2 years) adherence in hypertensive patients. The review also describes a not fully clear individualized approach, which consists in choosing a therapy regimen based on levels of medical adherence, medical follow-up and lifestyle modification.